Usefulness of the blink reflex to assess the effect of propofol during induction of anesthesia in surgical patients - Ferreira, Ana Isabel Leitão (2021)
MEDICON 2019 : XV Conferência Mediterrânea sobre Engenharia Médica e Biológica e Computação